Solving the Diamond-Mortensen-Pissarides model accurately - Nicolas Petrosky-Nadeau; Lu Zhang (Quantitative Economics, 2017)
An accurate global projection algorithm is critical for quantifying the basic moments of the Diamond-Mortensen-Pissarides model. Log linearization under- states the mean and volatility of unemployment, but overstates the volatility of labor market tightness and the magnitude of the unemployment-vacancy correlation. Log linearization also understates the impulse responses in unemployment in recessions, but overstates the responses in the market tightness in booms. Finally, the second-order perturbation in logs can induce severe Euler equation errors, which are often much larger than those from log linearization.
Keywords: E24; E32; J63; J64; 330; Search frictions; unemployment; projection; perturbation; nonlinear dynamics; parameterized expectations; finite elements